Wydział Teologiczny Papieskiej Akademii Teologicznej w Krakowie - Mieczkowski, Janusz; Szczurek, Jan (Studia Nauk Teologicznych PAN, 2020)
It was at the request of Blessed Queen Hedwig and her husband Jagiełło that on 11 January 1397 Pope Boniface IX signed a bull allowing foundation of the Faculty of Th eology in Kraków. Th is very date begin a six hundred years’ periodof the Faculty’s activities. Unfortunately in 1954 the Faculty of theology was removed by the unilateral edict of the communist Cabinet. Th is decision, however, did not cease the actual and canonical existence of the faculty. In 1959 the Apostolic See issued a decree stating that the Faculty of Th eology in accordance with its Founding Charter and character “remains under the supervision of one ecclesiastic authority and in the future is to be formed according to the laws passed by the Apostolic see”. In 1974 owing to the eff orts of Cardinal Karol Wojtyła the Faculty was bestowed the honourable title Pontifi cal. A turning point in the history of the Faculty of Th eology in Kraków came when on 8 December 1981 the Holy father issued a Motu proprio Beata Hedvigis in virtue of which the Pontifi cal Academy of Th eology with three faculties: theology, philosophy and Church history was establish. Th e aim of this Faculty of Th eology is to provide versatile and systematic knowledge of God’s revelation, its sources, message and forms of transmission, the attitude of man towards God revealing himself to him and the many forms of this Revelation in various centuries and ways of Church life. In studies leading to acquire Master’s degree, which lasts six years, there are mainly alumni preparing for priesthood coming from diocesan and religious seminaries as well as theological institutes affi liated with the Academy. Th ere are also theological studies for laity and nuns who have graduated from the Inter-Congregational Higher Education of Catechetic. Th e Faculty includes the following 32 chairs which are grouped in 8 specializations: biblical theology, fundamental theology, dogmatic theology, moral theology, theology of spirituality, practical theology, liturgy and canon law. Besides within the Faculty there are: Institute of Liturgy, Institute of Family and Institute of Canon Law. Th e Faculty has contracts with 15 seminaries for candidates for ordained ministry and 4 institutes of higher theological education which allow them to graduate their alumni. Aft er the removal from the University the Faculty has graduated 11 105 people (ordained and lay people) in the theology, it has also conferred 308 doctorate degrees in theology (DD) and 85 degrees of habilitation. In 2007 there was 1396 students. Th e Faculty has the accreditation of University Accreditation Commission (UAC). Th e Faculty is also member of Conference of Catholic Th eological Institutions (COCTI). It collaborates also wit diff erent foreign faculties, especially within the LLP-Erasmus (the EU Programm).